Dietary Supplementation of Mixed Yeast Culture Derived from Saccharomyces cerevisiae and Kluyveromyces maxianus: Effects on Growth Performance, Nutrient Digestibility, Meat Quality, Blood Parameters, and Gut Health in Broilers - Hao-Yang Sun; In-Ho Kim (The Journal of Poultry Science, 2019)
This study aimed to evaluate the effect of dietary supplementation of a mixed yeast culture (MYC; Saccharomyces cerevisiae YJM1592 and Kluyveromyces maxianus TB7258 in a 1:1 ratio) on growth performance, nutrient digestibility, meat quality, blood parameters, and gut health of broiler chickens. In total, 576 one-day-old male broilers (Ross 308) with an average initial bodyweight (BW) of 37±0.51 g were used in a 35-day experiment with a completely randomized design. The broilers were randomly assigned to 3 dietary treatments: CON, basal diet; TRT1, CON + 0.1% MYC; and TRT 2, CON + 0.2% MYC. From days 8 to 21, the feed conversion rate (FCR) was significantly decreased in broilers fed MYC-supplemented diets. From days 22 to 35, BW gain (BWG) significantly increased with increasing MYC concentration. Throughout the experiment, BWG increased (linear effect, P=0.002) and FCR decreased with increasing MYC in the diet. MYC supplementation increased the digestibility of dry matter (DM) in broilers in a dose-dependent manner. Relative organ weight of the bursa of Fabricius linearly increased in broilers fed MYC-supplemented diets. The white blood cell count showed linear and quadratic increases in broilers fed increasing concentrations of MYC. The population of Lactobacillus in the excreta linearly increased P=0.033, whereas that of Escherichia coli tended to linearly decrease (P=0.064) in the MYC groups. This study provides a basis for future research on MYC as a growth promoter in broilers.